Prediction of stiffness and stresses in z-fibre reinforced composite laminates - Grassi, Marcello; Zhang, Xiang; Meo, Michele (Elsevier Science B.V., Amsterdam., 2002)
The mechanical properties of z-pinned composite laminates were examined numerically. Finite element calculations have been performed to understand how the through-thickness reinforcement modifies the engineering elastic constants and local stress distributions. Solutions were found for four basic laminate stacking sequences, all having two percent volume fraction of z-fibres. For the stiffness analysis, a micromechanicalfinite element model was employed that was based on the actual geometric configuration of a z-pinned composite unit cell. The numerical results agreed very well with some published solutions. It showed that by adding two percent volume fraction of z-fibres, the through-thickness Young’s modulus was increased by 22-35 percent. The reductions in the in-plane moduli were contained within 7-10 percent. The stress analysis showed that interlaminar stress distributions near a laminate free edge were significantly affected when z-fibres were placed within a characteristic distance of one z- fibre diameter from the free edge. Local z-fibres carried significant amount of interlaminar normal and shear stresse